El Excentrico, 1977-02-05 - Garcia, Bert:::Publisher:::::::::::: (San Jose, California; Garcia Printing, 2024)
February 5, 1977 [5 de febrero de 1977]. Ano 27, No 20. Cover contains a portrait of Dr. Theodore Murguia, who was the first and only Mexican-American president of San Jose City College.